Analisis Customer Journey Map untuk Meningkatkan Customer Experience pada Real Estate Marketplace - Sayyidah Maulidatul Afraah; Zahwa Putri Aghniya (Program Studi Teknik Industri Universitas Setia Budi, 2025)
The development of innovation in the property sector has driven the emergence of various property technology startups. A total of 32 startups have been established, 24% of which operate as marketplaces. One of the main challenges faced by property or real estate marketplaces is enhancing customer experience (CX), which plays a crucial role in the complex process of property transactions. This study aims to analyze the customer journey map (CJM) of a real estate marketplace startup, referred to as PT X. The suboptimal CX processes at PT X have led to a low transaction rate. This research comprises four main stages: data collection and processing, customer journey mapping, pain point analysis using Failure Mode and Effect Analysis (FMEA), and the development of improvement recommendations through a service blueprint. The study identifies two major pain points affecting CX: the presence of false or irrelevant information due to the absence of an automated data verification system, and a search algorithm that does not prioritize listings with complete information. The Risk Priority Numbers (RPN) for these pain points are 512 and 448, respectively. Based on the analysis, the proposed recommendations include developing an automated verification system to ensure data validity and optimizing the search algorithm to prioritize listings with high-quality information. The implementation of these recommendations is expected to address the issues, enhance PT X's platform competitiveness, and provide a better user experience in meeting property needs.